2017
DOI: 10.1128/mcb.00481-16
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Hypoxia-Inducible Factor 2α Facilitates the Progression of Colon Tumors through Recruiting Neutrophils

Abstract: Inflammation is a significant risk factor for colon cancer. Recent work has demonstrated essential roles for several infiltrating immune populations in the metaplastic progression following inflammation. Hypoxia and stabilization of hypoxiainducible factors (HIFs) are hallmark features of inflammation and solid tumors. Previously, we demonstrated an important role for tumor epithelial HIF-2␣ in colon tumors; however, the function of epithelial HIF-2␣ as a critical link in the progression of inflammation to can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
49
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 59 publications
0
49
0
2
Order By: Relevance
“…Furthermore, MAZ was shown to have cell-autonomous regulation of cell growth in colon cancer cells both in vitro and in vivo. Recently, our work suggested an important role for MAZ in the inflammatory progression of colon cancer by regulating HIF-2␣-mediated expression of the potent neutrophil chemokine gene Cxcl1 (10). In the present study, we have discovered a novel HIF-2␣-independent function for MAZ in the regulation of STAT3 signaling.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Furthermore, MAZ was shown to have cell-autonomous regulation of cell growth in colon cancer cells both in vitro and in vivo. Recently, our work suggested an important role for MAZ in the inflammatory progression of colon cancer by regulating HIF-2␣-mediated expression of the potent neutrophil chemokine gene Cxcl1 (10). In the present study, we have discovered a novel HIF-2␣-independent function for MAZ in the regulation of STAT3 signaling.…”
Section: Discussionmentioning
confidence: 50%
“…MAZ splice variants 1 and 3 are activated by inflammation, whereas MAZ2 is anti-inflammatory (8,9). Our previous work has identified an essential role for MAZ in hypoxia-driven inflammatory responses in both colitis and colon cancer (10). MAZ is a direct protein interactor of hypoxia-inducible transcription factor 2␣ (HIF-2␣) and is important for HIF-2␣ transactivation of inflammatory target genes such as the tumor necrosis factor ␣ gene (Tnfa) (11,12).…”
mentioning
confidence: 99%
“…and DMF. We have previously shown that HIF-2α is a critical transcription factor involved in colon cancer progression 46 . Our drug screen data on enteroids from a hypoxic colon cancer mouse identifies erastin, RSL3, sorafenib and DMF as major molecules that could significantly reduce the growth of these hypoxic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor size and level of hypoxia can also establish the extent or type of neutrophil recruitment. Hypoxia‐inducible factor (HIF)‐2α expression in epithelial cells leads to colon tumor formation and expression of CXCL1 . In the KRAS/p53 genetic model of lung carcinogenesis, large tumors contain more neutrophils than small tumors.…”
Section: Recruitment Of Neutrophils To the Tumor Microenvironmentmentioning
confidence: 99%
“…Hypoxia-inducible factor (HIF)-2 expression in epithelial cells leads to colon tumor formation and expression of CXCL1. 102 In the KRAS/p53 genetic model of lung carcinogenesis, 103 large tumors contain more neutrophils than small tumors. This ability of larger, more hypoxic tumor to attract neutrophils is due to HIF-1 -induced Snail, which induces Cxcl2 expression in both the tumors and neutrophils.…”
Section: Recruitment Of Neutrophils To the Tumor Microenvironmentmentioning
confidence: 99%